The shearing modes approach to the theory of the diocotron instability of the cylindrical electron layer - Mykhaylenko, V.V.; Hae June Lee; Mykhaylenko, V.S.; Azarenkov, N.A. (Вопросы атомной науки и техники, 2013)
The temporal evolution of the linear diocotron instability of the cylindrical annular plasma column, which is driven by the shear of the equilibrium velocity of pure electron non-neutral plasma in crossed external magnetic and own electric fields, is investigated by using the extension of shearing modes methodology onto the cylindrical geometry. That approach does not use any spectral transforms in time and gives the solution of the initial value problems for any desired time. The evolution process leads toward the convergence to the phase-locking configuration of the mutually growing eigen and forced modes.